VALIDATION AND ANALYSIS OF AFLATOXIN B1 BY INDIRECT COMPETITIVE ENZYME-LINKED IMMUNOSORBENT ASSAY IN URINE SAMPLES FROM CHILDREN IN LONDRINA, PARANÁ STATE, BRAZIL - Ishikawa, Angélica Tiemi; Redondo, Estéfany Santos; Yamashita, Cassia Reika Takabayashi; Ono, Elisabete Yurie Sataque; Itano, Flávio Hiroshi; Souza, Bianca Dorana de Oliveira; Ono, Mario Augusto; Kawamura, Osamu; Hirooka, Elisa Yoko; Itano, Eiko Nakagawa (Seven Editora, 2024)
Aflatoxins (AFs), secondary metabolites produced by fungi of the genus Aspergillus spp., are recognized worldwide as a public health problem due to their potent carcinogenic, hepatotoxic, and immunosuppressive effect. Aflatoxin contamination in children is of particular concern given the negative impacts on health, development, and quality of life. The objective of this study was to validate the indirect competitive enzyme-linked immunosorbent assay (ic-ELISA) for the analysis of aflatoxin B1 (AFB1) in urine, as well as to evaluate the level of this mycotoxin in 150 urine samples from children living in Londrina, Paraná State, Brazil. The analytical performance parameters evaluated in the validation included specificity (matrix interference and comparison of curves with and without matrix), accuracy (recovery test), precision (repeatability and intermediate precision), robustness, sensitivity, linearity, limit of detection (LD) and limit of quantification (LQ). In the intralaboratory validation, matrix interference was analyzed with dilution factors of 2, 5 and 10 times, and the 5-fold dilution was selected to proceed. The standard curves prepared in the presence and absence of a matrix did not show significant differences in the percentage of linkage between the six points analyzed (p > 0.05). The average recovery rate for urine samples contaminated with AFB1 at concentrations of 1.0; 2.5 and 5.0 ng/mL were 100.00 ± 8.71%, 90.00 ± 2.00%, and 93.66 ± 1.52%, respectively. The coefficients of variation of the precision parameters were less than 15%. The regression equation obtained from seven standard curves was y=−14.89ln(x)+61.234y = -14.89 (x) + 61.234y=−14.89ln(x)+61.234, with a coefficient of determination (R²) greater than 0.99. The LD was 0.096 ng/mL and the LQ was 0.115 ng/mL. AFB1 was detected in 39.3% of the samples analyzed, with concentrations ranging from 0.13 to 9.40 ng/mL and an average of 1.63 ± 1.57 ng/mL. Based on the results obtained, the validated ic-ELISA proved to be adequate for the determination of AFB1 in infant urine. Preliminary data suggest that the level of aflatoxin contamination in children in the region of Londrina, Paraná, Brazil, is low. DOI: https://doi.org/10.56238/sevened2024.037-218